Parental support: prevention of cyber grooming in junior high school adolescents - Dini Rakhmawati; Venty Venty; Jovitha Julienjatiningsih; Mujiyono Mujiyono; Argo Widhiharto (Indonesian Institute for Counseling, Education and Therapy (IICET), 2023)
Social media has become an important part of human life, especially teenagers. Adolescents are vulnerable to manipulation on social media by adults for financial gain or sexual gratification that ends in sexual abuse. Research on cyber grooming in Indonesia is still limited. This research was conducted with correlational studies. The study population was 768 students of SMP N 6 Semarang. The sampling technique used was simple random sampling by taking 20% of the total population of 154 students. The method of data collection is carried out using psychological scale instruments. Data analysis techniques use correlation. Results showed that there was a positive association between parental support and supervision of adolescents' understanding of the dangers of cyber grooming. Parents' awareness of the risks of online or the risks of social media use in adolescents needs to be increased.